At the Crossroads: Human Rights of Romani Women in South East Europe: На крстопати: Човековите права на жените Ромки во Југоисточна Европа - Perić, Tatjana; Kovačić, Marina (Identities: Journal for Politics, Gender and Culture, 2005)
Author(s): Tatjana Perić | Татјана Периќ Title (English): At the Crossroads: Human Rights of Romani Women in South East Europe Title (Macedonian): На крстопати: Човековите права на жените Ромки во Југоисточна Европа Translated by (English to Macedonian): Marina Kovačić | Марина Ковачиќ Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005) Publisher: Research Center in Gender Studies - Skopje and Euro-Balkan Institute Page Range: 129-162 Page Count: 33 Citation (English): Tatjana Perić, “At the Crossroads: Human Rights of Romani Women in South East Europe,” Identities: Journal for Politics, Gender and Culture, Vol. 4, No. 1-2 (Summer - Winter 2005): 129-162. Citation (Macedonian): Татјана Периќ, „На крстопати: Човековите права на жените Ромки во Југоисточна Европа“, превод од англиски Марина Ковачиќ, Идентитети: списание за политика, род и култура, т. 4, бр. 1-2 (лето - зима 2005): 129-162.